Mining-induced deformation for a haulage drift of the hanging wall at Jinshandian iron mine in China - Yang, Kuoyu; Chen, Congxin; Sun, Yuliang; Xia, Kaizong; Wang, Tianlong (Frontiers in Earth Science, 2023)
In this paper, mining-induced deformation for haulage drifts of the hanging wall at Jinshandian Iron Mine is investigated, based on 8 monitoring stations adopted laser convergence meters. Monitoring results are analyzed to divide deformation-time curves into three types: fluctuation type, partial folding type and whole folding type. Moreover, it is found that tensile deformation is easy to occur in the roadway section corresponding to no folding type and partial folding type. And in the roadway section with folding type curve, it is obviously affected by the steeply anti-inclined structural plane. Furthermore, the relative position relationship between mining activities and a monitoring station is established through local coordinate system. Mining effects on roadway deformation are studied based on rectangular coordinate components and polar coordinate components respectively. The critical value of coordinate components that have a significant impact on roadway deformation have been determined. At last, combined with results of mining impact analysis, deformation mechanisms corresponding to the three deformation curves are revealed. These results help determine the appropriate support time and adopt targeted support schemes.